SECURITY CHANGES AND TRENDS IN NORTHEAST ASIA - Amartur Boldbaatar,; Enkhbaysgalan Bayasaa, (International Journal of Innovative Technologies in Social Science, 2025)
The changes and future trends in the security environment of Northeast Asia, as one of the most complex geopolitical regions in the world, have a significant impact on the international security situation. In recent years, the security situation in Northeast Asia has changed and become volatile due to the influence of internal and external factors. This article analyzes the changes in the security environment of Northeast Asia, examines future trends, and puts forward proposals for necessary measures.